Gatekeepers in the Field of Artificial Intelligence Technologies - Jovanović, Nikola (Digital Platforms: Legal And Economic Challenges, 2024)
The article examines the impact of generative artificial intelligence (AI) technologies on the economy and highlights the trends determined by this technology. The article points out the inability of existing competition rules to address the challenges of modern technology development. It analyzes the position of dominant companies in the artificial intelligence market. Global companies are actively striving to integrate generative artificial intelligence into their operations and service offerings provided to users. However, due to the complexity of technologies, only a small number of companies can develop generative artificial intelligence technologies. This could lead to market dominance by a very small number of powerful companies. The article emphasizes the urgency of regulation and legislative response to rapidly developing technologies. In particular, it highlights the EU's Digital Markets Act as an existing key regulatory tool. It emphasizes the need to consider including services related to generative artificial intelligence among core platform services.